2022
DOI: 10.1136/ip-2022-044714
|View full text |Cite
|
Sign up to set email alerts
|

Tackling sport-related concussion: effectiveness of lowering the maximum legal height of the tackle in amateur male rugby – a cross-sectional analytical study

Abstract: ObjectiveRugby union (‘rugby’) is popular globally, with most of its participants being amateur. Concern regarding sport-related concussion (SRC) sustained during rugby is increasing. SRC occurs most frequently in the tackle, yet few interventions have aimed to mitigate this risk factor. This study investigated the influence of a lowered legal tackle height on SRC incidence in amateur rugby.DesignCross-sectional analytical study: 2018 (control—standard tackle height) and 2019 (intervention—lowered legal tackle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…14,21,22 Another measure aimed at reducing the risk of concussion during the tackle was implementing a lowered maximum legal tackle height law variation trial (lowering the maximum legal tackle height from the ball carrier's shoulder level to armpit level). 23,24 These two studies, which are to date the only lowered maximum legal tackle height trials reported in professional and amateur rugby union, did not reduce the incidence of concussion in the studied cohorts. Despite being based on sound empirical evidence, 18 this intervention has not yielded a clear effect on concussion incidence, highlighting that implementing such a law variation trial is complex and involves various stakeholders.…”
Section: Introductionmentioning
confidence: 82%
“…14,21,22 Another measure aimed at reducing the risk of concussion during the tackle was implementing a lowered maximum legal tackle height law variation trial (lowering the maximum legal tackle height from the ball carrier's shoulder level to armpit level). 23,24 These two studies, which are to date the only lowered maximum legal tackle height trials reported in professional and amateur rugby union, did not reduce the incidence of concussion in the studied cohorts. Despite being based on sound empirical evidence, 18 this intervention has not yielded a clear effect on concussion incidence, highlighting that implementing such a law variation trial is complex and involves various stakeholders.…”
Section: Introductionmentioning
confidence: 82%
“…For example, to enhance player welfare standards, Word Rugby operates an internal research programme. Some research they have undertaken recently includes trialling the use of tackle-law changes to reduce concussion risk,45 understanding the collision demands at different levels of play46 and examining World Rugby’s Head Injury Assessment protocol to strengthen diagnostic accuracy 41 47. Partnerships with sports governing bodies are desirable because they have the resources to implement innovation nationally and globally, for example, New Zealand Rugby and the Accident Compensation Corporation partnered together to develop and deliver RugbySmart: a Nationwide Sports Injury Prevention Programme in New Zealand 48.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study in amateur level players found that lowering the legal tackle height to the armpit resulted in fewer upright tackles, suggesting player behaviour change, but a non-significant reduction in concussion incidence. 18 19 …”
Section: Discussionmentioning
confidence: 99%